Multicultural Education and Religious Tolerance: Elementary School Teachers’ Understanding of Multicultural Education in Yogyakarta - Sugeng Bayu Wahyono; Asri Budiningsih; Suyantiningsih Suyantiningsih; Sisca Rahmadonna (Al-Jami'ah Research Centre, 2022)
This study is about multicultural education and religious tolerance in the midst of increasing religious intolerance in the educational environment. This study analyses elementary school teachers’ understanding of multicultural education and its implementation. The research method is a case study in the city of Yogyakarta, chosen because it is both know as a city of education and because this city has declared it a tolerant city. The results showed that the understanding of elementary school teachers’ multicultural education is generally essentialist, but some were constructivist or anti-essentialist. The attitudes and actions of elementary school teachers, both consciously and unconsciously, may also include religious intolerance. One of the factors that distinguishes the content of religious tolerance and intolerance among elementary school teachers is their attitudes and actions towards local cultural principles. The higher the appreciation of local culture, the greater amount of religious tolerance. Further, when appreciation of local cultural traditions is low, it is more likely that a teacher is intolerant of other religions. [Tulisan ini membahas pendidikan multikultural dan toleransi beragama ditengah meningkatnya intoleransi di lingkungan pendidikan. Fokus tulisan ini adalah pemahaman guru sekolah dasar mengenai pendidikan multikultural dan implementasinya dengan studi kasus di kota Yogyakarta, karena kota ini adalah kota pendidikan dan mendeklarasikan sebagai kota toleran. Hasilnya menunjukkan bahwa pemahaman guru sekolah dasar mengenai pendidikan multikultur cenderung esensialis, tapi beberapa yang lain anti esensialis atau konstruktif. Sikap dan perilaku mereka baik sadar atau tidak sadar, mengandung kecenderungan intoleransi. Salah satu faktor yang membedakan muatan toleransi dan intoleransi diantara guru tersebut adalah sikap dan perilaku pada prinsip budaya lokal. Apresiasi tinggi pada budaya lokal adalah terbesar dalam toleransi beragama. Lebih lanjut, jika apresiasi pada tradisi lokal rendah, ini berarti guru tersebut cenderung intoleran pada agama lain.]